Optimization of a Rhabdomyolysis Model in Mice With Exertional Heat Stroke Mouse Model of EHS-Rhabdomyolysis - He, Si-Xiao; Li, Ru; Yang, Huo-Hong; Wang, Zi-Qing; Peng, Yan-Mei; Huang, Jun-Hao; Ma, Qiang (Frontiers in Physiology, 2020)
Exertional heat stroke (EHS) is a life-threatening disease characterized by high mortality and incidence of rhabdomyolysis (RM). It would therefore be valuable to establish a stable EHS-induced RM model that accurately reflects the clinical characteristics of EHS patients and provides an objective animal model for further study of the pathogenesis of RM. In the current study, 8~9-week-old, male, wild-type C57BL/6J mice, at the stage of sexual maturity, were randomly divided into four groups: the EHS group, the classical heat stroke (CHS) group, the sham heat exercise group, and sham heat rest group. The survival rate of mice was determined under relatively high levels of temperature and humidity (37.5°C, 65% relative humidity (RH); 37.5°C, 70% RH; 39.5°C, 65% RH; and 39.5°C, 70% RH) as well as a high core temperature (Tc; 42°C, 42.5°C, and 43°C). Results showed that the environmental condition of 39.5°C and 65% RH was most suitable for EHS modeling. The end point of EHS evaluation was exhaustion or an individual’s core temperature reaching 43°C. The survival rate of mice in the EHS group within 24 h under these conditions was 37.34%, which is consistent with the high mortality characteristics noted in EHS patients. Severe RM was observed in the EHS group by H&E staing and transmission electron microscopy. Creatine kinase levels in the EHS group mostly exceeded 10,000 U/L, which was approximately 10 times higher than that in the sham heat rest group.Renal tubules of the EHS group exhibited severe necrosis, and calcium overload in the skeletal muscles of this group was also observed using intravital 2-photon microscopy. In conclusion, we made improvements to a stable EHS-induced RM animal model to truly reflect the clinical characteristics of EHS patients. This new model should be helpful in the further study of RM pathogenesis.